Psych. The complete second season [videorecording (DVD)] - Bernsen, Corbin, 1954-; Hill, Dulé; Roday, James; Lawson, Maggie; Brocklebank, Sage (Universal Studios Home Entertainment, 2011)
Shawn Spencer is on the case again! Quick-witted Shawn and his skeptical best friend Gus race to solve crimes while deceiving the police into believing in Shawn's so-called psychic abilities. Special features include deleted scenes, audio commentaries, gag reel, and more.